(untitled) (Marketing Journal, 2025)
This article analyzes the formation and development trends of the e-commerce sector in the Republic of Uzbekistan, as well as the existing challenges and ways to overcome them. It also highlights the role and importance of information and communication technologies (ICT) in the creation of e-commerce infrastructure. The article presents an analysis of digital payment systems, mobile applications, internet platforms, and data security issues, emphasizing the role of innovative technologies as a key factor in increasing the efficiency of electronic commerce. The study concludes with practical recommendations for further development of e-commerce in Uzbekistan.